Five new species of Polana (Polana) (Hemiptera: Cicadellidae: Gyponini) from Brazil and Costa Rica, and new combinations in the genus - Domahovski, Alexandre Cruz (Zootaxa, 2025)
The subgenus Polana comprises 34 species, of which only five are currently recorded in Brazil. In this work five new species are described in the subgenus Polana of which P. torta sp. nov. is from Costa Rica and four are from Brazil: P. inflexa sp. nov. from Distrito Federal and states of Mato Grosso do Sul, Goiás, and Paraná; P. insolita sp. nov. from states of Goiás and Mato Grosso do Sul; P. languida sp. nov. from states of Mato Grosso and Rondônia; and P. sinopensis sp. nov. from state of Mato Grosso. New distribution records are given and five species are newly recorded from Brazil: P. coresa DeLong & Freytag, 1972; P. innata DeLong & Foster, 1982; P. mala DeLong & Freytag, 1972; P. scruta DeLong & Freytag, 1972; and P. squalera DeLong & Freytag, 1972. Additionally, P. flectara DeLong & Freytag, 1972 and P. fusconotata (Osborn, 1938) have new records to Brazilian states. The following new combinations are proposed: three species of the subgenus Polana—P. ocellata (Spångberg, 1878), P. villara DeLong, 1979, and P. pravida DeLong & Foster, 1982 are transferred to the subgenus Nihilana; three species of the subgenus Nihilana—P. onara DeLong & Triplehorn, 1979, P. robusta DeLong, 1980, and P. thugana DeLong & Triplehorn, 1979 are transferred to the subgenus Polana; five species of the subgenus Polana—P. caputa DeLong, 1980, P. carla DeLong, 1980, P. diversita DeLong & Wolda, 1982, P. julna DeLong & Wolda, 1982, and P. tinae DeLong & Wolda, 1982 are transferred to the subgenus Polanana; one species of the subgenus Polanana—P. chena DeLong & Wolda, 1978 is transferred to the subgenus Hobemanella; seven species not placed in subgenera are here designed as follows: P. cumbresa DeLong & Wolda, 1984 and P. gatunana DeLong & Wolda, 1984, are placed in Bulbusana; P. censora DeLong & Wolda, 1984 is placed in Hobemanella; and P. boquetea DeLong & Wolda, 1984, P. calvanoa DeLong & Wolda, 1984, P. clavata DeLong & Wolda, 1984, and P. miramara DeLong & Wolda, 1984 are placed in Polanana. Polana (Hobemanella) ardua DeLong & Freytag, 1972 and Polana (Varpulana) elera DeLong & Freytag, 1972 are considered incertae sedis within Polana. A key to males of the subgenus Polana is provided.